A cross-sectional study of the relationship between facial wrinkles and osteoporosis among individuals referred for bone densitometry - Ebrahimzade-Ardakani, Mohammad; Ashabi, Fatemeh; Pezeshkian, Fatemehsadat; Ghanei, Azam; Sahaf, Akram-Sadat; Ahramiyanpour, Najmeh (Journal of Pakistan Association of Dermatologists, 2023)
ABSTRACT Introduction: Osteoporosis is a systemic disease that leads to mechanical fractures by decreasing bone density. Postmenopausal women with fractures following osteoporosis reportedly have thinner skin. This study evaluated the relationship between bone density and facial wrinkles. Methods: We conducted an analytical-cross-sectional study featuring 427 patients aged 40–80 referred to a bone density measurement center in Yazd in 2021. Demographic and clinical data were collected using a questionnaire. A dermatologist assessed wrinkles in 11 zones of the face as per the Lemperle scale. Results: The mean age of the participants was 69.63 years, with a slight female predominance noted (57%). The mean lumbar T-score was -2.69 ± 0.71, and the mean femoral T-score was -2.69 ± 0.72. Facial wrinkles increased with age and negatively correlated with lumbar and femoral T-scores. The findings were replicated after adjusting for other effective risk factors such as connective tissue/bone disorders, diabetes, corticosteroid use, and smoking. Conclusion: The increase in facial wrinkles with aging was associated with a decline in bone density in those at risk of osteoporosis. This observation could assist in accounting for facial wrinkles as a risk factor for osteoporosis, so that earlier diagnosis and intervention could be initiated. Longitudinal studies should further investigate this association